Pengembangan Media Pembelajaran Berbasis Aplikasi Menggunakan Powerpoint Mata Pelajaran IPA - Setiawati, Nofi; Astrida, Kiki; Ali Fikri, Achmad (N A T U R A L: Jurnal Ilmiah Pendidikan IPA, 2022)
Technological know-how mastering can be supported by using the usage of getting to know media. instructors can use gaining knowledge of media as practical equipment to carry cloth, modern and appropriate learning media are capable of foster interest in gaining knowledge of technology. The cause of this observe became to determine student responses to the product evolved and to describe the improvement of software-based totally gaining knowledge of media using valid Powerpoint so that students should use them in understanding technological know-how subjects. This look at makes use of a 4D version that has 4 stages, specifically outline, layout, broaden and disseminate. This improvement studies or RND is only as much as the expand degree. This take a look at makes use of data series strategies, particularly statement, interviews, and questionnaires or questionnaires. The records analysis method used on this studies is quantitative and qualitative descriptive analysis. The outcomes of the examine resulted in utility-based mastering media merchandise the usage of powerpoint technology topics. Validation become done through media professionals and cloth experts in addition to teachers in science topics. The results of the validation and testing on 10 students at MTs NU Banat Kudus were given a terrific response and on the feasibility of the usage of the product it become suitable to be used as a gaining knowledge of medium. The feasibility of the product obtained based totally on the assessment of media experts and fabric specialists were given a median value of 3.eighty in the suitable class, the assessment through the technological know-how instructor obtained a mean value of three.78 the price changed into in the exact category, the evaluation of the feasibility of interactive mastering media products turned into based totally at the check. try grade IX students at MTs NU Banat Kudus obtained three.89 inside the very good.      Keywords: Application-based learning media, Powerpoint, Science subjects